Black glasses grafted micron silicon: a resilient anode material for high-performance lithium-ion batteries. Issue 30 (18th July 2022) - Nandan, Ravi; Takamori, Noriyuki; Higashimine, Koichi; Badam, Rajashekar; Matsumi, Noriyoshi
Abstract : Effective methodology for designing a resilient micron silicon-based anode material for stable and reversible storage of lithium ions and its practical application in next generation lithium-ion batteries. Abstract : Despite its rich natural abundance and high gravimetric capacity, the adoption of silicon (Si) anodes in transformative technologies like lithium-ion batteries (LiBs) has been largely hindered due to their mechanical instability and subsequent dynamic solid electrolyte interphase (SEI) formation. These demerits are amplified many times over when we move from nanostructured Si to otherwise cost-effective and user-friendly micron Si particles (SiMPs). Maintaining the coalescence in fracture-prone SiMPs to avoid/delay pulverization as well as accommodating the lithiation-driven stress demands judicious material design for any possible commercial adoption of SiMPs in the near future. Herein, inspired by the appealing structural features of silicon oxycarbide black glasses (BGs), we proposed a facile and rational design strategy via the thoughtful grafting of carbon-coated SiMPs (Si/C) using acetylene black-embedded BG (ABG, i.e., Si/C/ABG) to address the two essential requirements of (i) structural intactness and subsequent (ii) stable solid electrolyte interphase formation by internally stabilizing the fracture-prone SiMPs and externally providing a stable electrolyte–material interface. Benefiting from superior lithium diffusion kinetics, suppressed overall volumetric expansion, reduced internal resistance and rapid improvement in initial coulombic efficiencies, Si/C/ABG demonstrates excellent rate capabilities in combination with appreciable capacity retention ability (∼99.4% post 775 th cycle at 750 mA g −1 ), thus demonstrating its utility for possible practical adoption in commercial LiBs. Importantly, this study further reveals the successful integration of Si/C/ABG as a negative electrode in a full-cell when paired with a commercially available lithium nickel cobalt aluminium oxide (NCA) cathode and exhibits appreciable rate and cycling performances. Overall, the present methodology offers an effective avenue for developing/designing resilient micron-sized silicon anodes and can be swiftly extended to a variety of other potent high-capacity micron-sized anode materials.